Electrical and electromagnetic characteristics of poly (methyl methacrylate)/polyaniline PMMA/PANi conductive film - Abu Hassan Shaari, Helyati; Ramli, Muhammad Mahyiddin; Mohtar, Mohd Nazim; Abdul Rahman, Norizah; Ahmad, Azizan; Osman, Nurul Huda (UiTM Press, 2023)
In this study, a conductive film of poly (methyl methacrylate)/polyaniline (PMMA/PANi) was fabricated through a free radical copolymerization reaction using methyl methacrylate (MMA) and aniline monomers at different aniline-to-MMA ratios, namely, 1:1, 1:3, and 1:5. The PMMA/PANi copolymer films exhibited a total electromagnetic interference (EMI) shielding effectiveness (SET) of 0.45, 0.60, and 1.22 dB, respectively, which is more than twice that of the pure PMMA film (0.16 dB). The copolymer films possess the highest conductivity of 2.34 x 10−6 S/cm at the optimum value of aniline for films polymerized with a 1:3 PMMA:PANi ratio. Higher conductivity materials exhibited lower resistance and, thus, absorbed more EM energy, resulting in better EMI shielding.